Charging of dust grains weakly ionized plasma - J, Vanchinkhuu; L.N, Hau (Scientific transaction of the National University of Mongolia. Physics, 2022)
The charging of dust grains in weakly ionized high pressure plasma is considered in drift-diffusion approximation which is valid for dusty plasma under high pressure as atmospheric plasma. The dependence of dust potential on the number density of grains and the temporal evolution grain charge are taken. It is shown that the charging time of grain in high pressure plasma is smaller than that of grain in low pressure plasma. By using the Poisons equation, the potential distribution around the dust particle is taken.